Nilai-nilai Pendidikan Akhlak Dalam Qs. Al Baqarah - Hidayat, Syarif (Al-Riwayah : Jurnal Kependidikan, 2016)
Value can be divided into two kinds, namely the divine values and Insaniyah value. The divine value is the value that comes from faith (revelation of God), while the Insaniyah value is the value created by man on the basis of criteria that are created by man as well. The divine value can be divided into two kinds; the first is ubudiyah value, that is the value of how one should apply and worship to God. Ubudiyah value we often refer to as “hablum minallah”. The second is muammalah value that is determined by God for man to be used as guidelines in dealing with the social environment. The Insaniyah value consists of rational values, social values, individual values, biophysical value, and economic value, political value and aesthetic values. This value can also called the “hablum minannnas” Of the two types of value above, the value of the Divine is a value that no longer is subjective but became objective on certain religious circles. This article examines the issue of value-in-charge of Islamic education, particularly in the surah al-Baqarah.